Konsep Muhkam dan Mutasyabih (Studi Komparatif Pemikiran Syaikh Manna’ al-Qahthani dan Nasr Hamid Abu Zayd) - Rifqy Amru Rasyidi Yunus; Munawir Munawir (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited comparative research between classical and modern Islamic scholars in understanding the concepts of muhkam and mutasyabih in the Qur’an, despite the fact that differing approaches to these concepts have significant implications for interpretative methodologies and the meaning of revelation in contemporary contexts. The aim of this study is to compare the interpretations of muhkam and mutasyabih according to Shaykh Manna’ Khalil Al-Qaththan and Nasr Hamid Abu Zayd. A descriptive qualitative method was employed using a library research approach, focusing on content analysis of the scholars’ key works—Mabahits fi ‘Ulum al-Qur’an by Al-Qaththan and Mafhum an-Nash by Abu Zayd. Data were collected through the review of journals, books, proceedings, and other relevant sources, and analyzed descriptively and analytically by comparing previous findings and synthesizing both thinkers’ perspectives. The results show that Al-Qaththan defines muhkam as verses that are clear, decisive, and foundational to Islamic legal rulings, while mutasyabih refers to ambiguous verses whose true meanings are known only to Allah. In contrast, Abu Zayd views muhkam and mutasyabih as symbols of textual dialectics that are inherently open to multiple interpretations, with meaning formed through the interaction between the text, the reader, and the socio-historical context. The main conclusion of this research is that an integrative understanding of muhkam and mutasyabih combines the theological firmness of Al-Qaththan’s classical perspective with the contextual interpretive flexibility of Abu Zayd. The implication of this study lies in its methodological contribution to the development of an integrative model of Qur’anic exegesis, enabling wise, relevant interpretations of the sacred text while maintaining the authority of revelation amid the dynamics of contemporary religious life.